Spin-Resolved Electronic Response to the Phase Transition in MoTe2 - Weber, Andrew P.; Ruessmann, Philipp; Xu, Nan; Muff, Stefan; Fanciulli, Mauro; Magrez, Arnaud; Bugnon, Philippe; Berger, Helmuth; Plumb, Nicholas C.; Shi, Ming; Blügel, Stefan; Mavropoulos, Phivos; et al. (PHYSICAL REVIEW LETTERS, 2018)
The semimetal MoTe2 is studied by spin- and angle-resolved photoemission spectroscopy across the centrosymmetry-breaking structural transition temperature of the bulk. A three-dimensional spin- texture is observed in the bulk Fermi surface in the low temperature, noncentrosymmetric phase that is consistent with first-principles calculations. The spin texture and two types of surface Fermi arc are not completely suppressed above the bulk transition temperature. The lifetimes of quasiparticles forming the Fermi arcs depend on thermal history and lengthen considerably upon cooling toward the bulk structural transition. The results indicate that a new form of polar instability exists near the surface when the bulk is largely in a centrosymmetric phase.